2019
DOI: 10.1002/jcb.28877
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids plus piperine improve nonalcoholic fatty liver disease: A clinical trial

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) as a prevalent hepatic disease is associated with an increased risk of morbidity and mortality related to the liver and cardiovascular disease (CVD). Lifestyle modification and good metabolic control is the first line of treatment, but not always efficacious in reversing NAFLD pathogenesis. Curcumin is a dietary phytochemical with hepatoprotective activities, though its low bioavailability is considered as a major challenge for clinical applications. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 30 publications
2
37
1
Order By: Relevance
“…Similarly, a combined therapy of curcuminoids and piperine was effective against nonalcoholic fatty liver disease (Panahi et al, 2019). In type 2 diabetes mellitus, piperine and curcuminoids mutually modulated the adipokines and controlled the energy metabolism (Panahi et al, 2017).…”
Section: Combinational Therapy Using Piperinementioning
confidence: 99%
“…Similarly, a combined therapy of curcuminoids and piperine was effective against nonalcoholic fatty liver disease (Panahi et al, 2019). In type 2 diabetes mellitus, piperine and curcuminoids mutually modulated the adipokines and controlled the energy metabolism (Panahi et al, 2017).…”
Section: Combinational Therapy Using Piperinementioning
confidence: 99%
“…However, a profitable effect was also found on NAFLD severity. 32 Furthermore, Pezeshki et al 33 proposed that green tea, a rich source of catechin, could improve serum levels of liver enzymes in patients with NAFLD and they studied administration of green tea extract (500 mg per day) or a similar placebo for 90 days. At the end of the trial, AST, ALP and ALT levels were significantly reduced in the supplement group.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy adults were arbitrarily assigned to the placebo or treatment group and consumed one capsule after meals for 12 weeks. Results showed that the administration of Curcumin C 3 Complex ® and Bioperine ® improved liver and lipid profile without altering hematological parameters, thus reducing NAFLD severity compared to placebo [73]. The same research group also considered the effect of the formulation on serum inflammatory factors, namely, TNFα and IL-6, in a randomized double-blind placebo-controlled trial with 55 subjects with NAFLD.…”
Section: The Early Factors Impacting Metabolismmentioning
confidence: 99%